SELECTION OF THE BEST PREWEDDING PHOTO LOCATION USING THE AHP METHOD - Muhammad Noval Alfarizi; Mariah Nur Azizah; Wikara Dwi Saputra; Siti Ernawati (Kresnamedia Publisher, 2021)
The location of the photo prewedding is a place that can describe the happiness of the bride and groom. In these conditions sometimes the general public especially prospective bride and groom and the photographer have difficulty in choosing the location of the photo prewedding best. Then the resulting decision-makers will get the location of the photo prewedding which is not in accordance with what is expected. In this study utilizes the Method of Analytical Hierarchy Process (AHP) to help the bride and groom and the photographer in choosing the location of the photo prewedding best, especially in the area of Jakarta. This study using six criteria such as distance, number of spots, transportation, time, cost, location, and theme. From the Results of the analysis and processing of the data obtained that the Ancol with superior value 0,224047721 (22%) berbandingan to cafe batavia with a value of 0,195494507 (20%), sunda kelapa harbor to the value 0,187335550 (19%), taman wisata mangrove angke kapuk with a value of 0,171584976 (17%), old city, with the value of 0,162696386 (16%), and glodok, with a value of 0,058840858 (6%).